Optimal design configuration of corona rings for 1200 KV bus post insulators. (October 2022) - Radhika, G.; Raja Nayak, M.; Saritha, M.; Padma, Rowthu; Nagaraju, T.; Santhosh Kumar, T.
Abstract: Estimation and regulation of the electric field stresses at ultra-high voltage levels are vital to achieve the reliable power system operation. Designing of the sustainable ultra-high potential equipment's are the major challenge for the design engineers to satisfy the modified power demand scenario. The substation bus post insulator is the one of the key devices supports to achieve the sustainable and reliable power system operation. The severe problem in designing of the station post insulator at ultra-high potential ratings is its field stresses. To control these severe field stresses, significant electrodes like bus conductors, toroid rings, grading rings and corona rings are essential. The appropriate selection of these high potential electrode dimensions supports the optimal economic power system operation: failure reports the catastrophic behaviour of the station bus post insulators. Hence, the significant research knowledge on optimal size of high potential electrodes of substation bus post insulators at Extra and ultra-high potential levels is necessary before designing of these high voltage electrodes. Usually, it is a tedious process to attain the optimal design dimensions and its positions of the high potential electrodes in the actual field. Thus, the sophisticated numerical analysis-based simulation studies provide significant support to obtain the optimal size of high potential electrodes of bus post insulators at ultra- high potential ratings. Therefore, this paper aims to present the numerical based simulation design and its study of the high potential electrodes of the 1200 kV substation bus post insulator. Multiple design configurations of the electrodes like various corona ring, grading ring, bus conductor diameters and its positions are considered and compared to analyse the effect of the electrical stress, potential distribution variation of the 1200 kV bus post insulator. Therefore, from the simulation investigations, the optimal design data configuration of high potential electrodes for 1200 kV substation bus post insulator was suggested. Also, the high voltage electrode design configuration of proposed 1200 kV insulator followed by the one of the manufacturing industries is tested and compared.